Pelatihan Pembuatan Lesson Plan dan Media Pembelajaran bagi Guru di Sekolah Dasar Negeri 34 Pontianak Kota - Dwi Fajar Saputri; Syarifah Fadillah; Nurhayati Nurhayati; Nurussaniah Nurussaniah (Universitas Prof. Dr. Hazairin, SH, 2019)
Workshop on Creating Lesson Plans and Making Learning Media for Teachers at 34 Elementary Schools in Pontianak City Teachers still have difficulty in making learning tools with the conditions of students in the class, and teachers have limitations in making learning media. The purpose of this program was to increase teacher knowledge about creating lesson plans and learning media. The method was training and mentoring held for two months from planning to evaluation. Fourteen elementary school teachers attended the training as participants. Pre-test and post-test were done to evaluate teacher knowledge about lesson plans. This community service was useful, and it can be concluded that this activity increased teacher knowledge about making learning tools. The teacher's knowledge score during the pre-test, ie, before training, was 57,87 points. The score at the post-test increased to 73,61. The teacher was skilled at making learning media materials so that they were available to students at affordable prices and attractive designs.